QUALIDADE DO TUBÉRCULO DO INHAME SOB NÍVEIS DE IRRIGAÇÃO E DIFERENTES TIPOS DE SOLO - Li, Meiling; Deus, Angélia Cristina Fernandes; Ming, Lin Chau; Barbosa, Aline Gonçalves (IRRIGA, 2022)
CORM QUALITY OF TARO UNDER IRRIGATION LEVELS AND DIFFERENT SOIL TYPES MEILING LI1，3；ANGÉLICA CRISTINA FERNANDES DEUS2；LIN CHAU MING3 E ALINE GONÇALVES BARBOSA3 1Information Research Institute of Science and Technology, Shanghai Academy of Agricultural Sciences, Jinqi Road, 1000. Zip-Code: 201403, Fengxian, Shanghai, China. Tel: +0086-15316186815; Email: limeilinghappy@126.com 2Department of Plant Health, Rural Engineering, and Soils, College of Engineering, São Paulo State University, Monção Street, 226, Zip-Code: 15385-000, Ilha Solteira, São Paulo, Brazil. Email: angelica.deus@unesp.br. 3Department of Horticulture, Agronomical Sciences College, São Paulo State University, Universitária Avenue, 3780, 18610-034, Botucatu, SP, Brazil. Email: linmin2809@gmail.com; 260292239@qq.com. 1 ABSTRACT Irrigation amount is an important factor in the development of taro, however, there is little information focus on effects of water levels affect on its corm quality under different soil textures. Thus, this study aimed to evaluate the taro corm quality in response to five irrigation levels (20%, 60%, 100%, 140% and 180% ETc - crop water requirement) under three soil textures. Results indicated that corm number total (CNt) and diameter (CD) of taro decreased with reduced irrigation levels, higher values were detected at 140%ETc and 180%ETc. CD and CNt performed better in sandy soil than in other two soils, especially in irrigation level lower than 100%ETc. In general, total sugar (TS), reducing sugar (RS), and starch content (SC) of taro corm performed better in higher water regime, except that for protein content (PC). Taro corm had higher TS and SC in sandy soil, while lower PC was observed in the same soil treatment. Overall, higher water level was more beneficial to improve corm quality, and SS could be more suitable for taro cultivation under water stress. Keywords: water stress, soil texture, colocasia esculenta l. schott. LI, M.; DEUS, A. C. F.; MING, L. C.; BARBOSA, A. G. QUALIDADE DO TUBÉRCULO DO INHAME SOB NÍVEIS DE IRRIGAÇÃO E DIFERENTES TIPOS DE SOLO 2 RESUMO A irrigação é um fator importante no desenvolvimento de taro, no entanto, há poucas informações sobre os efeitos de lâminas de irrigação em diferentes texturas do solo. O objetivo do estudo foi avaliar a qualidade dos tubérculos de inhame em resposta a cinco níveis de irrigação (20%, 60%, 100%, 140% e 180% ETc - necessidade hídrica da cultura) e três texturas de solo. O número de tubérculo (CNt) e o diâmetro (CD) diminuíram com os menores níveis de irrigação, os maiores valores foram detectados em 140%ETc e 180%ETc. CD e CNt tiveram melhor desempenho em solo arenoso do que nos outros dois solos, especialmente com lâmina de irrigação inferior a 100%ETc. Em geral, o teor de açúcar total (TS), açúcar redutor (RS) e teor de amido (SC) do tubérculo tiveram melhor resultado com maior lâmina de irrigação, exceto para o teor de proteína (PC). O tubérculo apresentou maior TS e SC em solo arenoso, enquanto menor PC foi observado no mesmo tratamento de solo. No geral, o nível de água mais alto foi mais benéfico para melhorar a qualidade do tubérculo, e o solo arenoso pode ser mais adequado para o cultivo de taro sob estresse hídrico. Palavras-chave: estresse hídrico, textura do solo, colocasia esculenta l. schott.